Root characteristics in cowpea related to drought tolerance in seedlings - Matsui, T.; Singh, B.B. (Cambridge University Press, 2003)
Cowpea (Vigna unguiculata) has relatively higher drought tolerance than other legume crops. It is widely grown in semi-arid regions, particularly in West Africa. One objective of the present study was to determine the effects of soil moisture stress on the length, dry matter and distribution of the roots of two cowpea varieties with different drought tolerances. Another objective was to evaluate the pin-board root-box as a method for identifying the role of root characteristics in drought tolerance. Two cowpea varieties, IT96D-604 (drought tolerant) and TVu7778 (drought susceptible), were used in this study. There were three watering treatments, T1 (well-watered), T2 (mild water stress) and T3 (severe water stress). Between varieties, there were no significant differences in shoot and root characteristics except for leaf area in T1. Under T2, the shoot : root ratio (S : R ratio) of IT96D-604 was significantly decreased compared with that under T1 as a result of the increase in root dry matter and decrease in leaf area without significant differences in total dry matter. In addition, the root dry matter per leaf area, which indicates the capacity to absorb water, of IT96D-604 was significantly higher than that of TVu7778. Under T3, the total dry matter of TVu7778 was about one third of those of the other treatments for the same variety, whereas that of IT96D-604 was more than half. Regarding root distribution, the centres of root dry matter and root length density of both varieties moved downwards significantly under water-stress conditions compared with those of the well-watered condition. This tendency was more pronounced in IT96D-604 than in TVu7778. Drought tolerance in IT96D-604 was associated with the increase in root dry matter per leaf area under mild water-stress conditions, and downward movement of roots (increasing access and use of soil moisture in deep soil layers) under mild and severe water stress conditions. In addition, the root-box method was versatile and can be used for studying root responses to edaphic factors relevant to root growth.